TAREKAT NAQSABANDIYAH KHALIDIYAH DI SLEMANAN KABUPATEN BLITAR - Romzan Fauzi (Balai Penelitian dan Pengembangan Agama Semarang, 2008)
This research on Tarekat Naqsabandiyah Khalidiyah locatedin Sleman, Blitar, Blitar has aim to describe Tarekat NaqsabandiyahKhalidiyah group that covering several aspects. The descriptionsinclude brief history of the tarekat, observance of religious dutiesof the tarekat, tarekat groups, and their relation with other parties.This tarekat is established initially by K.H. Abdul Ghafur, andcurrently is lead by Mursid K.H. Abdul Gafur bin K.H. Abdul.Ghafar. Observances of religious duties include bai 'at, dzikir; andkhalwat or suluk. Followers come from neighborhood area andoutside that area.